Effect Of Polyethylene Glycol And Silica-Based Flame Retardant Materials On Properties Of Ultraviolet Curable Palm Oil Resin - Sua, Pei Ru (2017)
An ultraviolet curable palm oil resin (POR) was formulated by modifying palm oil with glycerol and reacted with glycidyl methacrylate (GMA). Polyethylene glycol (PEG) and silica based monomers (silanes) were employed in the formulation as softening and flame retardant agents. The silanes were vinyl trimethoxysilane (VTMS), trimethoxy phenylsilane (TMPS) and tetramethoxy silane (TMOS). The physical, mechanical, thermal stability and flame retarding properties of Si-POR were studied. The results showed POR with PEG has smaller molecular weight and polydispersity index (PDI) ranged from 1.69 to 2.30. It was noticed that iodine number of POR was greater than 130g I2/100g oil and can be characterized as drying oil, though the iodine number was declined slightly in the addition of PEG.